Enhancement of the strength–ductility trade-off in a heterogeneous medium Mn steel through multiple synergistic effects of deformation mechanisms - Hao Chen; Haifeng Xu; Wenquan Cao; Caidong Zhang; Shenghai Lu; Zejun Chen (Journal of Materials Research and Technology)
In this work, multiple deformation/strengthening mechanisms were developed into medium manganese steel (MMnS) based on a simple cold-rolling and intercritical annealing process. The prepared MMnS comprises of bimodal heterogeneous austenite encompassing approximately 60% coarse grains and 40% fine grains. The heterogeneous design tailors the diverse austenite stability to achieve sustained and multilevel strain-induced martensitic transformation (SIMT), balancing the strain hardening ability, ductility and fracture. Preferably, the strengthening of fine austenite includes the twinning-induced plasticity (TWIP) effect, stacking fault networks, Lomer–Cottrell (L–C) locks, and nano-VC particles, while coarse austenite only triggers the transformation-induced plasticity (TRIP) effect. The heterostructured steel achieved an ultrahigh tensile strength of over 1.5 GPa, and an excellent elongation of 49.6% due to the multiple synergistic effects of deformation mechanisms. Our results indicated that the coordination of multiple mechanisms may be an effective method to enhance the strength–ductility trade-off of MMnS.